An intramolecular C(sp3)–H imination using PhI–mCPBA. Issue 14 (28th January 2019) - Bose, Anima; Maiti, Saikat; Sau, Sudip; Mal, Prasenjit
Abstract : Development of sustainable methods for the activation of less reactive undirected C(sp 3 )–H bonds is challenging but desired in organic synthesis. The present manuscript demonstrates selective activation of acidic C(sp 3 )–H groups for a dehydrogenative C–H imination reaction by 4H elimination using PhI (10 mol%)– m CPBA as an organocatalyst. Abstract : Herein, a highly exothermic primary amine–polyvalent iodine reaction has been used successfully for selective functionalization of acidic C(sp 3 )–H groups for a dehydrogenative C–H imination reaction by 4H elimination. Overall, C(sp 3 )–H imination at 1, 5 distances was readily done via organocatalysis using PhI (10 mol%)– m CPBA under ambient conditions.